History as an Increasingly Complex System (2011)
The study of complex systems stands at the cross-border of various sciences, disciplines, methodologies and even logics. It has given birth, indeed, to border sciences and precisely, border problems. Complex systems, however, have mostly been studied and understood as part of the physical, mathematical, biological and computer sciences. Even though little attention has been paid to social sciences as complex systems in precisely the terms of the sciences of complexity, the number of books and articles on human social systems as complex systems has been raising in the last few years1. Nonetheless, there is almost no work concerning the relationship between complexity and history. Perhaps the most conspicuous text in this direction is I. Wallerstein‘s (1987), a short and cautious work. Even though we can encounter several articles and a few chapters in books dealing with history and chaos, there is no consensus so far as to the relation between history and chaos and, additionally and most important, there is no real and deep understanding of the relationship between chaos and complexity and, henceforth, between complexity and history. As for the rest, the links and matches between history and complexity are timid or avoid facing history as science vis-à-vis the question of complexity. At most, the writings available so far deal with history as a tool, for instance in treatments such as: “the history of complexity”, “complexity and economic history,” and the like. (1) (PDF) History and Complexity. Available from: https://www.researchgate.net/publication/264957479_History_and_Complexity [accessed Aug 26 2020].